cui prodest - Grigoryeva, Elena (project baikal, 2017)
As Bulgakov’s Yeshua said, there are no evil people. People always aim for goodness. But the problem is that the idea of goodness has not yet become common to all mankind. Sometimes, the notion of goodness has surprisingly controversial senses for different communities, groups of people, or different persons. The bloodiest wars and revolutions and the heaviest losses in cultural heritage of the mankind were caused by somebody’s pursuance of goodness and profit. In the 1st century AD, the famous Roman lawyer Cassian Longin Ravilla formulated a logical principle that makes it possible to figure out whose ideas of goodness and profit give rise to different phenomena of social life. From a logical point of view, this principle has its drawbacks: drought is profitable for a grain merchant, but he never causes the drought. However, the cui prodest principle often indicates the true causer of events and processes. Another lawyer, who was very famous in the early 20th century, often used this principle in political discussions and even made it a title of one of his polemical articles. There are a lot of people in the professional community who are very much concerned about the processes occurring in contemporary cities, about the situation in architectural and town-planning education in our country; who think that transformation of the status of the architect is dangerous, and who are not satisfied with the heritage practices. We are not going to limit ourselves to the search of those who are to blame for these negative processes. We believe that the analysis of the reasons and the benefits of all that is happening will allow us to see its logic and sense, its goals and triggers. As soon as we understand this, we’ll be able to influence it more effectively, for our common and long-term benefit.